SHAPING HYRULE: FAN AND GAME DEVELOPER CO-PRODUCTION OF NARRATIVE AND WORLD IN THE LEGEND OF ZELDA - Labrador, Margarita (Journal of English Studies and Comparative Literature, 2019)
This paper explores how the The Legend of Zelda franchise lends itself to the creation of a master timeline through the use of repeated elements in both gameplay and storyline. Using Otsuka Eiji’s “World and Variation”, I demonstrate how Nintendo’s design philosophy of “game play before story line” creates a formula, or a Zelda “world” from which the game developers make the “variations” that become each unique game in the series.